Bamomong Dalam Kajian Bentuk dan Fungsi Pada Upacara Pernikahan Di Nagari Bayua, Kecamatan Tanjung Raya - Sari, Gustika; Ediwar, Ediwar; Desmawardi, Desmawardi (Institut Seni Indonesia Padangpanjang, 2024)
This research aims to describe the form and function of the baby in wedding ceremonies in Nagari Bayua, Tanjung Raya District, Agam Regency, besides that the baby is also used in local communities such as inauguration of events such as: welcoming guests, baduduak activities, and other related activities with Alek Nagari. This research uses qualitative research methods with data collection techniques through observation, documentation and interviews in the field to obtain research results according to descriptive context. The results of this research explain the form and function of children in wedding ceremonies in Nagari Bayua, Tanjung Raya District, Agam Regency.